2007
DOI: 10.1111/j.1740-8261.2007.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Two Methods for Assessing Thyroid‐lobe Asymmetry During Pertechnetate Scintigraphy in Suspected Hyperthyroid Cats

Abstract: Our aim was to investigate thyroid:thyroid (T:T) ratio and visual inspection for assessing thyroid-lobe asymmetry in suspected hyperthyroid cats. Although thyroid-salivary asymmetry is a preferred test, inherent thyroid symmetry may assist image interpretation. Association was determined using a scatter plot and Spearman's rank correlation. Agreement was assessed using the kappa (K) statistic. Accuracy was assessed by sensitivity and specificity. Hyperthyroidism was diagnosed in 33/48 (69%) cats based on eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Uptake of 99m TcO 4 − by the thyroid in normal dogs is described as symmetric 13,15,16,27 . Asymmetric thyroid uptake of 99m TcO 4 − has been found in animals with thyroid neoplasia or hyperthyroidism and in normal cats 28 . The reason for the asymmetry noted in the present study is unclear but it likely represents a normal feature of greyhounds.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Uptake of 99m TcO 4 − by the thyroid in normal dogs is described as symmetric 13,15,16,27 . Asymmetric thyroid uptake of 99m TcO 4 − has been found in animals with thyroid neoplasia or hyperthyroidism and in normal cats 28 . The reason for the asymmetry noted in the present study is unclear but it likely represents a normal feature of greyhounds.…”
Section: Discussionmentioning
confidence: 41%
“…13,15,16,27 Asymmetric thyroid uptake of 99m TcO 4 À has been found in animals with thyroid neoplasia or hyperthyroidism and in normal cats. 28 The reason for the asymmetry noted in the present study is unclear but it likely represents a normal feature of greyhounds. A difference in thyroid lobe volume might be the cause of the asymmetry.…”
Section: Discussionmentioning
confidence: 67%
“…66 Recently it has been reported that at least some euthyroid cats have asymmetric thyroid lobes during visual inspection of pertechnetate scintigrams. 68 Margins of the thyroid lobes should be smooth and regular. Ectopic thyroid tissue is not usually seen in normal cats.…”
mentioning
confidence: 99%
“…A normal thyroid scintigram in cats shows the two thyroid lobes as elongated, oval structures in the cervical region, smoothly delineated, symmetrical in size and position and with a homogeneous distribution of the radionuclide (Figure 2). A certain level of thyroid lobe asymmetry can be present in euthyroid cats (Scrivani et al, 2007). Ectopic thyroid tissue is less commonly seen.…”
Section: Thyroid Scintigrammentioning
confidence: 99%
“…In the literature, the potential role of the thyroid:thyroid (T:T) ratio in the diagnosis of hyperthyroidism has been reported only once (Scrivani et al, 2007). The T:T ratio refers to a lobe-to-lobe ratio, where the value of the most active thyroid lobe is divided by the value of the less active lobe.…”
Section: Quantitative Thyroid Scintigraphymentioning
confidence: 99%